Thomas Hardy : une écriture paradoxale entre génération et dégradation entropique - Annie Escuret (Cahiers Victoriens et Edouardiens)
Thomas Hardy is a figure of transition caught between a classic type of mimetic aesthetic and a modern type of aesthetic. Just like Turner, he did manage to disrupt the aesthetics of classic realism when he gave up writing novels and wrote The Dynasts. The term « modernism » surfaced in Tess of the D’Urbervilles (1891) when the narrator complains about the creeping industrial « ache of modernism ». Modernity stands for an aesthetic of change, experimentation, ephemerality and insecurity. Hardy’s works do belong to the condemnatory, apocalyptic and despairing trend that will culminate with T. S. Eliot or W. B. Yeats. If Joyce did manage to create new myths, in Jude the Obscure Hardy chose blasphemy. Mikhail Bakhtin (1895-1975) used Einstein’s ideas of space-time to coin the term « chronotope » to refer to his theory of the distinctive use of topology in particular genres of fiction. Hardy’s Wessex is a poetic creation that generates a new sort of time and space. Some of Hardy’s narratives do not belong to this modern conception of time : when time means loss in Hardy’s fiction, it refers to thermodynamics and to the loss of energy, that is to say time as degradation and no longer time as poetic creation embodied in Hardy’s Wessex.